Health Status of Older Adults with Hypertension after Family and Cadre Empowerment through Comprehensive Care - Komang Ayu Henny Achjar; Lita Heni Kusumawardani; Sri Astiti Padma Parashita (Media Karya Kesehatan, 2022)
A decrease in both physiological and psychological functioning in older adults necessitates a family's assistance to improve their health status in order to maintain the condition and care of   older adults with degenerative diseases that are often experienced with hypertension. Hypertensive management consists of pharmacological and non-pharmacological therapy which requires dynamic treatment. The purpose of this research is to determine the effects of family and cadre empowerment on older adults with hypertension's health status in Bali Province. The method used pre-post-test quasi experiment with control group design and it involved 62 older adult respondents and family in the province of Bali. Data was analysed by dependent and independent t-test as well as double logistic regression test. Analysis results showed there was a significant influence from the intervention on older adult health status. The multivariate test also discovered that the age of the older adult also affects the increase in older adult health status. It is expected that this program can be implemented in health services and developed into a more dynamic program. Keywords: Empowerment, health status, older adult.